Assess the awareness of COVID-19 among the physiotherapists working in different hospitals of Sindh, Pakistan: A cross sectional survey - Aadil Ameer Ali; Sana Naqi; Muhammad Khan Bugti; Muhammad Rafeeq; Muhammad Ishaque M.R; Taufiq Ahmad; Amjad Hussain; Shabana Yasmeen; Hafsa Imtiaz Khokhar (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2021)
Background: To assess the awareness of Covid-19 among the Physiotherapists of Sindh, Pakistan, in order to check the level of knowledge present regarding the pandemics among the working physiotherapist of Pakistan. Material & Methods: A cross sectional study was carried out in different hospitals of Sindh, Pakistan from June to July 2020. A self-constructed questionnaire by Pursuing the clinical and community administration of COVID-19 given by the National Health Commission of the People's Republic of China was used among the 343 Physiotherapists and SPSS version 23 was used to analyze the data. Results: The majority (n=207, 60.3%) were male, having age between 33 and above years (n=227, 66.2%) and (n=304, 88.6%) were married. In educational status (n=230, 67.1%) were postgraduate and (n=304, 88.6%) belongs to urban area. During the assessment of awareness towards COVID-19 results showed that majority (n=321, 93.6%) were aware of COVID-19. Conclusion: This Study concluded that the physiotherapists who are working in different hospitals of Sindh, Pakistan are well aware of COVID-19.The awareness can be due to their self-interest in infection preventive measure and quality of education being provided by their respective institutions.